Effects of Different Light Spectra on Oxidative Stress and Nutritional Quality of the Fish Plectropomus leopardus - Wensheng Li; Zheng Zhang; Baoliang Liu; Yingying Fang; Shuquan Cao; Wenyang Li; Yan Sun; Chengbin He; Chuanxin Zhang; Fan Fei (Fishes, 2024)
This study investigated the impacts of light spectra on oxidative stress and nutrient quality of the fish Plectropomus leopardus in indoor recirculating aquaculture systems. The fish (100 g ± 0.45 g [wet weight]) were cultures in five different light spectra (full-spectrum (400–800 nm), blue (450 nm), green (530 nm), red (630 nm), and dark) for 60 days. After experimentation, blood and muscle tissue were collected and analyzed for biochemical variables and nutritional quality. We demonstrated that the total cholesterol, triglycerides activities of P. leopardus in the dark groups were substantially elevated, relative to other groups (p